Characterization of MicroRNA Cargo of Extracellular Vesicles Isolated From the Plasma of Schistosoma japonicum-Infected Mice - Li, Shun; Giri, Bikash R.; Liu, Jingyi; He, Xiaobing; Cai, Pengfei; Jing, Zhizhong; Cheng, Guofeng (Frontiers in Cellular and Infection Microbiology, 2022)
Schistosoma is a genus of parasitic trematodes that undergoes complex migration in final hosts, finally developing into adult worms, which are responsible for egg production and disease dissemination. Recent studies documented the importance of extracellular vesicles (EVs) in the regulation of host-parasite interactions. Herein, we investigated the microRNA (miRNA) profiles of EVs isolated from host plasma at different stages of Schistosoma japonicum infection (lung stage: 3 days post-infection (dpi), and liver stages: 14 and 21 dpi) to identify miRNA cargo potentially involved in the pathogenesis and immune regulation of schistosomiasis. Characterization of the isolated plasma EVs revealed their diameter to be approximately 100 nm, containing typical EV markers such as Hsp70 and Tsg101. Deep sequencing analysis indicated the presence of 811 known and 15 novel miRNAs with an increasing number of differential miRNAs from the lung stage (27 miRNAs) to the liver stages (58 and 96 miRNAs at 14 and 21 dpi, respectively) in the plasm EVs of infected mice compared to EVs isolated from the uninfected control. In total, 324 plasma EV miRNAs were shown to be co-detected among different stages of infection and the validation of selected miRNAs showed trends of abundance similar to deep sequencing analysis. For example, miR-1a-3p and miR-122-5p showed higher abundance, whereas miR-150-3p and miR-126a showed lower abundance in the plasma EVs of infected mice at 3, 14, and 21 dpi as compared to those of uninfected mice. In addition, bioinformatic analysis combined with PCR validation of the miRNA targets, particularly those associated with the immune system and parasitic infectious disease, indicated a significant increase in the expression of Gbp7and Ccr5 in contrast to the decreased expression of Fermt3, Akt1, and IL-12a. Our results suggested that the abundance of miRNA cargo of the host plasma EVs was related to the stages of Schistosoma japonicum infection. Further studies on the roles of these miRNAs may reveal the regulatory mechanism of the host-parasite interaction. Moreover, the differentially abundant miRNA cargo in host EVs associated with S. japonicum infection may also provide valuable clues for identifying novel biomarkers for schistosomiasis diagnosis.